Gastrointestinal Haemorrhage in Children: A Retrospective Study of 64 cases (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
SUmmary: In a study of 64 children admi tted to the Ahmadu Bello University Teaching Hospital, Zaria, with gastrointestinal bleeding over a 7-year period, it was found that the main causes of bleeding were portal hypertension (28.1%), infection (17.2%) haemorrhagic disease of the newborn (7.8%), neoplasm (6.3%) and aspirin ingestion (6.3%). Other causes of gastrointes tinal bleeding were peptic ulcer, blunt abdominal trauma and liver abscess. No cause was identified in 25% of the cases. The mortality was 9.4% and was associated with severe anaemia, while the coexistence of underlying disorders such as cyanotic heart disease and systemic infection probably worsened the prognosis in others.